2005
DOI: 10.1021/ja0444482
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of an Expanded Porphyrin That Has Selectivity for the c-MYC G-Quadruplex Structure

Abstract: Cationic porphyrins are known to bind to and stabilize different types of G-quadruplexes. Recent studies have shown the biological relevance of the intramolecular parallel G-quadruplex as a transcriptional silencer in the c-MYC promoter. TMPyP4 also binds to this G-quadruplex and most likely converts it to a mixed parallel/antiparallel G-quadruplex with two external lateral loops and one internal propeller loop, suppressing c-MYC transcriptional activation. To achieve therapeutic selectivity by targeting G-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
192
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(213 citation statements)
references
References 62 publications
15
192
0
4
Order By: Relevance
“…41,68-70 For example, cationic porphyrins and sapphyrins have been shown to bind to and stabilize a number of different types of G-quadruplexes. 41,44,71,72 Specifically, the cationic porphyrin and sapphyrin used in this study, TMPyP4 and Se2SAP, have been shown to have variable selectivity for G-quadruplex structures. TMPyP4 is less discriminating compared to Se2SAP, which has been shown to specifically stabilize one of the c-myc G-quadruplexes, 41 as well as the K + form of the human telomeric G-quadruplex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,68-70 For example, cationic porphyrins and sapphyrins have been shown to bind to and stabilize a number of different types of G-quadruplexes. 41,44,71,72 Specifically, the cationic porphyrin and sapphyrin used in this study, TMPyP4 and Se2SAP, have been shown to have variable selectivity for G-quadruplex structures. TMPyP4 is less discriminating compared to Se2SAP, which has been shown to specifically stabilize one of the c-myc G-quadruplexes, 41 as well as the K + form of the human telomeric G-quadruplex.…”
Section: Discussionmentioning
confidence: 99%
“…Se2SAP is a synthetic, core-modified, expanded porphyrin that was first synthesized in our laboratory with the specific aim of targeting a subset of G-quadruplex structures. 41 Telomestatin is a natural product, 51 which has been shown to inhibit telomerase through its strong G-quadruplex interaction with the human telomeric sequence. 52 DNA polymerase stop assays were preformed with this series of compounds together with the three individual G-quadruplex-forming sequences (5′G4, MidG4, and 3′G4) to test whether selective stabilization of specific G-quadruplexes was achievable (Figure 7).…”
Section: The Three Different G-quadruplex-forming Sequences Bind G-qumentioning
confidence: 99%
“…Owing to the unique secondary motif, G-quadruplex is impervious to be attacked by enzymes targeting normal single-stranded or duplex DNA, and consequently is able to regulate the transcription and replication of specific gene. Therefore, G-quadruplex motif attracts growing interests and the ligands able to stabilize or regulate the formation of specific G-quadruplex motifs have been considered as potential novel anticancer medicines [10][11][12].…”
mentioning
confidence: 99%
“…For example, telomestatin, a macrocyclic natural product comprising a similar structure to a G-tetrad, is currently regarded as a good G-quadruplex ligand and is the most efficient in vitro telomerase inhibitor [15][16][17]. Another important feature of G-quadruplex ligands is the central cationic aromatic core.…”
mentioning
confidence: 99%